Complete Genome Sequence of Streptomyces ambofaciens DSM 40697, a Paradigm for Genome Plasticity Studies - Thibessard, Annabelle (Genome Announc, 2016)
The sequence of Streptomyces ambofaciens DSM 40697 was completely determined. The genome consists of an 8.1-Mbp linear chromosome with terminal inverted repeats of 210 kb. Genomic islands were identified, one of which corresponds to a new putative integrative and conjugative element (ICE) called pSAM3.